2006
DOI: 10.1021/jo0607717
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of Enantiopure α-Trifluoromethyl Alanines, Diamines, and Amino Alcohols via the Strecker-type Reaction

Abstract: Diastereomerically pure alpha-trifluoromethyl alpha-amino nitriles obtained by Strecker-type reactions from chiral CF3 imines and iminium proved to be very attractive versatile intermediates for the synthesis of various alpha-trifluoromethyl amino compounds. From these synthons, both enantiomers of alpha-trifluoromethyl alanine, trifluoromethyl 1,2-diamines, and amino alcohols were conveniently obtained in enantiopure form in high yields in a few steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 26 publications
2
59
0
1
Order By: Relevance
“…In the course of our studies, we recently reported several approaches for the stereoselective synthesis of a-and btrifluoromethyl amino acids (Tfm AAs) starting from chiral CF 3 -oxazolidines (Fox) or imines [8]. Among them, we developed an efficient route for the synthesis of (S)-and (R)-a-Tfm proline based on the use of the key chiral CF 3 -hydroxymorpholinone 2 (Scheme 1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our studies, we recently reported several approaches for the stereoselective synthesis of a-and btrifluoromethyl amino acids (Tfm AAs) starting from chiral CF 3 -oxazolidines (Fox) or imines [8]. Among them, we developed an efficient route for the synthesis of (S)-and (R)-a-Tfm proline based on the use of the key chiral CF 3 -hydroxymorpholinone 2 (Scheme 1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of chiral optically pure amines as the chiral auxiliary for achieving the highly diastereoselective Strecker reaction has evolved into a relatively general and robust approach for accessing various enantiomerically pure α-amino acids. [12][13][14][15][16][17][18] The first example of a diastereoselective Strecker reaction assisted by a chiral auxiliary on the amine component was reported by Harada, who used (S)-1-phenylethylamine as the chiral auxiliary to obtain chiral (S)-α-amino acids after acid hydrolysis of the nitrile and cleavage and recovery of the N-alkyl group. …”
Section: Diastereoselective Strecker Reactionsmentioning
confidence: 99%
“…Карбамати із О-трет-бутильним замісником 3е,є можна розглядати як свого роду N-Boc-мо-нозахищені похідні і при дії насиченого хлоро-воднем розчину діоксану вони легко перетворю-ються на дигідрохлориди 2-арил-3,3,3-трифторо-пропан-1,2-діаміну 5а,б, спектральні характери-стики яких підтверджують їх будову. Запропоно-ваний спосіб одержання сполук такого типу ва-гомо доповнює описаний в літературі підхід, який передбачає окиснення відповідних 2-(2-гідрокси-1-фенілетиламіно)-3,3,3-трифторопропіл амінів тетраацетатом свинцю [19] (схема 3).…”
Section: таблицяunclassified